Hubungan Persepsi Alumni Terhadap Kompetensi yang Dikuasai Dengan Kompetensi yang Dibutuhkan Dunia Kerja - Meta Adilah; , Irmeilyana; , Ali Amran (UNIB Press, 2022)
The tracer study is a survey whose main object of research is graduates to evaluate the competitiveness of graduates on the relevance of competence to the needs of the world of work. This study aims to determine the tendency of differences in alumni perceptions on the level of mastered competence and the level of competence required by the world of work. This research data is in the form of answers to the 2020 tracer study questionnaire questions obtained from CDC Unsri. The research respondents were FMIPA graduates in 2018. This study uses the Wilcoxon test and correspondence analysis. The Wilcoxon test results show that there are 7 competency items that need to be improved to match the competencies needed by the world of work, namely: Knowledge in the field of science, knowledge outside the field of science, general knowledge, critical thinking skills, working independently, loyalty, and writing skills in reports, memos and documents. The results of the correspondence analysis show that for each competency item there is a relationship between the alumni's perception of the level of competence mastered and the level of competence needed by the world of work.